2022
DOI: 10.1111/jonm.13620
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life in nurses on the frontline against COVID‐19

Abstract: Aims This study aimed to investigate professional quality of life (ProQOL) in nurses who were fighting against COVID‐19 in Wuhan and its related factors. Background COVID‐19 epidemic is a major threat to public health. Frontline nurses have engaged in infection prevention and control, isolation, containment and public health. However, available data on ProQOL in these nurses are limited. Methods From 15 to 21 March 2020, the Chinese version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
0
22
1
Order By: Relevance
“…Nursing itself is a demanding profession that often requires nurses to meet the needs of patients and families before their own needs ( Mullen, 2015 ). Although frontline nurses during the COVID-19 pandemic reported high levels of compassion satisfaction with their work, there was a high prevalence of secondary traumatic stress ( Niu et al, 2022 ). This may also be true in academia where nurse educators may place the needs of the institution, program, and students before meeting their own individual needs which then impacts their personal life.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing itself is a demanding profession that often requires nurses to meet the needs of patients and families before their own needs ( Mullen, 2015 ). Although frontline nurses during the COVID-19 pandemic reported high levels of compassion satisfaction with their work, there was a high prevalence of secondary traumatic stress ( Niu et al, 2022 ). This may also be true in academia where nurse educators may place the needs of the institution, program, and students before meeting their own individual needs which then impacts their personal life.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the WLQ of those who said that their workload increased because of the COVID-19 pandemic was found to be low. It was reported in another study conducted with nurses working in hospitals in China during the COVID-19 pandemic that participants with long working hours and heavy workloads had low WLQ (Niu et al 2022 ). In support of the findings of the present study, in the study conducted by Kılıç and Keklik ( 2012 ) with healthcare employees, it was reported that employees who had intensive working hours had lower WLQ scores; and in the study conducted by Kaya ( 2011 ) with nurses, nurses working overtime had lower WLQ scores; and in the study conducted by Karadağ Öncel ( 2019 ) with pediatric assistants, it was reported that physicians with long working hours had negative effects on WLQ and lower WLQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang stated that reduced job satisfaction, compassion fatigue, and burnout are all directly correlated with the nursing profession's inherent stress and traumatic events [ 32 ]. Job satisfaction had a negative correlation with STS and CF [ 43 , 44 ]. Several studies found that stress is related to or affects STS and CS [ 45 , 46 ].…”
Section: Literature Reviewmentioning
confidence: 99%